2020
DOI: 10.1177/2167696820946597
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality and Identity Configurations: A Qualitative Study Exploring Sexual Identity Development Among Emerging Adults Within the United States

Abstract: Although modern comprehensive conceptual models of sexual identity development acknowledge contextual factors, existing models have placed less emphasis on (a) the influence of multiple domains of identity on sexual identity formation and (b) centrality and negotiation of various domains of identity. The present study sought to explore processes, identity conflicts, and management of sexual identity relative to other identity domains among sexual minority emerging adults in the United States. Fourteen sexual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…However, though Erikson categorizes the adolescent stage as a stage for identity development, one considers whether the narrative development of LGBTQ identity spans beyond the adolescent stage of psychosocial development. Parmenter et al (2020b) sought to understand identity development amongst young adults and found that, though participants were 20-25 years old therefore categorized as young adults in Erikson's intimacy versus isolation stage of development (Erikson, 1982), findings highlighted LGBTQ young adults' experiences of identity conflict and exploration. LGBTQ young adults expressed identity consolidation and conflicts in integrating their LGBTQ identity across their lives (Wagaman et al, 2016;Parmenter et al, 2020b).…”
Section: Erik Erikson's Stages Of Psychosocial Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, though Erikson categorizes the adolescent stage as a stage for identity development, one considers whether the narrative development of LGBTQ identity spans beyond the adolescent stage of psychosocial development. Parmenter et al (2020b) sought to understand identity development amongst young adults and found that, though participants were 20-25 years old therefore categorized as young adults in Erikson's intimacy versus isolation stage of development (Erikson, 1982), findings highlighted LGBTQ young adults' experiences of identity conflict and exploration. LGBTQ young adults expressed identity consolidation and conflicts in integrating their LGBTQ identity across their lives (Wagaman et al, 2016;Parmenter et al, 2020b).…”
Section: Erik Erikson's Stages Of Psychosocial Developmentmentioning
confidence: 99%
“…Parmenter et al (2020b) sought to understand identity development amongst young adults and found that, though participants were 20-25 years old therefore categorized as young adults in Erikson's intimacy versus isolation stage of development (Erikson, 1982), findings highlighted LGBTQ young adults' experiences of identity conflict and exploration. LGBTQ young adults expressed identity consolidation and conflicts in integrating their LGBTQ identity across their lives (Wagaman et al, 2016;Parmenter et al, 2020b). Particularly for LGBTQ young adults with intersecting ethnic or religious identities, their young adult experiences of identity integration were highly distressing and resulted in identity confusion (i.e., identity suppression, compartmentalization, and separation) and decreased levels of life satisfaction (Wagaman et al, 2016;Parmenter et al, 2020b).…”
Section: Erik Erikson's Stages Of Psychosocial Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative researches have studied understanding of experiences of the concept of frustration from a stance of emerging adults. Qualitative studies have permitted vast insight and understanding into complicated human behaviour compared to surveys and different quantitative measures of personal experiences (Denzin & Lincoln, 2000;Parmenter, Galliher, Yaugher, & Maughan, 2020). Izard (1993) proposed four components of the emotion model (subjective experience, physiological response, social expressive, purposive) for studying and understanding frustration employed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been increased awareness and affirmation of LGBTQ+ identities, LGBTQ+ individuals still experience discrimination within mainstream cis-heterodominant cultural spaces and feel motivated to conceal their identity to maintain safety. Research on LGBTQ+ individuals, especially LGBTQ+ emerging adults (Garvey et al, 2019; Parmenter et al, 2022; Peña-Talamantes, 2013), documents the impacts of oppressive sociocultural contexts on LGBTQ+ identity processes. Research on sexual identity development should begin to incorporate the process of negotiating (e.g., concealing or disclosing) sexual identity within the cis-heterodominant culture while maintaining and nurturing marginalized LGBTQ+ identities.…”
mentioning
confidence: 99%